Immunization with full-length Plasmodium falciparum merozoite surface protein 1 is safe and elicits functional cytophilic antibodies in a randomized first-in-human trial - Blank, Antje; Fürle, Kristin; Jäschke, Anja; Mikus, Gerd; Lehmann, Monika; Hüsing, Johannes; Heiss, Kirsten; Giese, Thomas; Carter, Darrick; Böhnlein, Ernst; Lanzer, Michael; Haefeli, Walter E.; et al. (npj vaccines, 2020)
A vaccine remains a priority in the global fight against malaria. Here, we report on a single-center, randomized, double-blind, placebo and adjuvant-controlled, dose escalation phase 1a safety and immunogenicity clinical trial of full-length Plasmodium falciparum merozoite surface protein 1 (MSP1) in combination with GLA-SE adjuvant.
Gesehen am 03.04.2020